2013
DOI: 10.1002/anie.201304561
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Diastereoselectivity in Enantioselective [4+2] Cycloadditions with Simple Olefins by Asymmetric Binary Acid Catalysis

Abstract: Chiral 3,4-dihydro-2H-pyrans and tetrahydropyrans are versatile structural motifs of a number of bioactive natural products (e.g. epicalyxin F and sugiresinol), [1,2] fragrances (doremox), [3] and foodstuff flavorings ( Figure 1). [4] A straightforward approach to access this type of products is the catalytic asymmetric inverse-electron-demand Diels-Alder reaction between a,b-unsaturated carbonyl compounds and alkenes. [5][6][7][8] Though extensively explored in asymmetric catalysis, [9] this reaction has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(33 citation statements)
references
References 75 publications
2
30
0
Order By: Relevance
“…Luo developed a Lewis acid‐dependent diastereodivergent IED Diels–Alder reaction of simple olefins with β,γ‐unsaturated α‐ketoesters based on synergistical combination of a chiral phosphoric acid 100 or calcium salt 101 and a Lewis acid (Scheme ) . The combination of In(BArF) 3 with the free phosphoric acid 100 delivered exo ‐adducts 102 .…”
Section: Lewis Acid‐controlled Diastereodivergencymentioning
confidence: 99%
“…Luo developed a Lewis acid‐dependent diastereodivergent IED Diels–Alder reaction of simple olefins with β,γ‐unsaturated α‐ketoesters based on synergistical combination of a chiral phosphoric acid 100 or calcium salt 101 and a Lewis acid (Scheme ) . The combination of In(BArF) 3 with the free phosphoric acid 100 delivered exo ‐adducts 102 .…”
Section: Lewis Acid‐controlled Diastereodivergencymentioning
confidence: 99%
“…We suspected that the Brønsted acidity of chiral phosphoric acid is not strong enough to simultaneously activate ketimine 1a and allylboronate 2a . Inspired by Luo's asymmetric binary acid catalysis (Lv et al., 2011, Lv et al., 2013, Hashimoto et al., 2013, Hatano et al., 2015, Wang et al., 2017, Zhang et al., 2017a) and the bismuth catalyzed allylation of para -quinone with allylboronate 2a developed by our group (Zhang et al, 2017b), we proposed that this transformation was likely to be promoted by the BiX 3 -chiral phosphoric acid catalyst system and the use of chiral phosphoric acid could ensure the stereochemistry of this process. Gratifyingly, in the presence of (S) - 5a and Bi(OAc) 3 , the model reaction gave product 3a in quantitative yield with 87.9: 12.1 er (Table 1, entry 3).…”
Section: Resultsmentioning
confidence: 99%
“…An estimation based on UV absorption showed that approximately 76% of TP dissociated into trityl cations in the presence of InBr 3 . On the other hand, tritylium salts with a weakly coordinating metal-based monophosphate or bisphosphate anion could also be obtained when trityl bromide was treated with the corresponding metal phosphate, which can be prepared in situ following our previously described procedure (Scheme 2,c) [3738]. UV analysis indicated that the indium salt 1a or gallium salt 1b (0.05 mM) could induce ca.…”
Section: Resultsmentioning
confidence: 99%